ICoN explores strategic networking for industry-community benefits - Siti Nurfarmy, Ibrahim (2019)
Acting as the liaison between academicians and the industries and communities, the Department of Industry Partnership and Community Relations (ICoN) at University Malaysia Pahang (UMP) has, this week, expanded its strategic networking to include a number of agencies in Sabah on March 19, 2019.